FV 15. Genome-wide association study of human brain arousal regulation. Issue 9 (September 2016) - Jawinski, P.; Sander, C.; Spada, J.; Ulke, C.; Mauche, N.; Huang, J.; Surova, G.; Burkhardt, R.; Kirsten, H.; Scholz, M.; Hensch, T.; Hegerl, U.
Abstract : Objectives: According to the Research Domain Criteria Project (RDoC), arousal is one principal dimension underlying psychiatric disorders. The Vigilance Algorithm Leipzig (VIGALL) is a novel LORETA-based computer algorithm, which enables to objectively measure brain arousal by means of electroencephalic activity. Notably, the spectral composition of electroencephalic activity is counted among the most heritable human traits. Getting beyond a prior candidate-gene approach, the present study aimed to further elucidate the molecular genetic architecture of human brain arousal regulation by conducting genome-wide association (GWA) analyses. Methods: Healthy participants ( N = 1786, 898 male, 40–79 yrs) of the population-based LIFE-Adult study underwent a twenty-minute eyes-closed resting EEG. Brain arousal was assessed using VIGALL 2.0. DNA was extracted from peripheral blood leukocytes. Genotypes were determined using the Affymetrix Axiom Genome-Wide CEU1 Array. Results: GWA analyses revealed rs74478422 in the estrogen receptor 1 gene surpassing the threshold of genome-wide significance ( p = 1.9E-8), with the minor allele being linked to generally lower levels of brain arousal across the twenty-minute resting EEG. Seven further loci reached sub-threshold significance ( p < 1E-6). Conclusion: The present study provides first evidence from GWA analyses for variations in the estrogen receptor 1 gene to impact human brain arousal regulation. In general, our results point to a polygenic contribution with various potentially involved loci of modest effect sizes. Acknowledgement: This publication is supported by LIFE – Leipzig Research Center for Civilization Diseases, Universität Leipzig. LIFE is funded by means of the European Union, by the European Regional Development Fund (ERDF) and by means of the Free State of Saxony within the framework of the excellence initiative.